Computational modelling studies of lithiated TiO2 nano-architectured structures at different temperatures, for energy storage applications - Rikhotso, Blessing Nkateko (My University, 2019)
Nano-architecture structures of LixTiO2 are very promising as anode materials for lithium rechargeable batteries due to their ability to accommodate more lithium atoms and its ability to withstand high temperatures at atomistic level through charging and discharging. In these studies, we investigated how nano-architectured structures of LixTiO2 behave at high temperatures through the process of amorphisation and recrystallisation. A computational method of molecular dynamics (MD) simulation was employed to recrystallise the amorphous LixTiO2 nano-architectures of bulk, nanosheet, nanoporous and nanosphere, where x depicts the fraction of lithium ions, i.e. 0.03, 0.04 and 0.07. The main objective of this study was to go beyond the previous inserted lithium atoms on TiO2 and understand the effects of concentrations, temperature, defect chemistry and charge storage properties/capacity on the overall lithium transport to improve lithium ion battery performance. Recrystallisation of all four nanostructures from amorphous precursors were successfully achieved and was followed by the cooling process towards 0 K and finally we heated all four nano-architectures at temperature intervals of 100 K up to 500 K. The variation of configuration energies as a function of time, was used to monitor the crystal growth of all nanostructures. Calculated Ti-O radial distribution function, were used to confirm the stability interaction after cooling. Calculated X-Ray Diffraction (XRD) spectra where used to characterise and compare their patterns at cooled and above high temperatures, using the model nanostructures, and they showed polymorphic nanostructures with LixTiO2 domains of both rutile and brookite in accord with experiment. Amorphisation and recrystallization showed good results in generating complex microstructures. In particular, bulk structures show few zigzag tunnels (indicative of micro twinning) with 0.03 Li but 0.04 Li and 0.07 Li show complex v patterns indicating a highly defected structure. While 0.03 and 0.04Li nanospheres show, zigzag and straight tunnels in accord with experiment, the one with 0.07 Li has melted. Lastly, nanoporous and nanosheet structures have pure straight and zigzag patterns that are well in accord with our XRD patterns at all concentrations of lithium atoms and temperatures. The lithium transport was analysed using diffusion coefficient, calculated as a function of temperature in order to confirm the mobility above the given temperatures. An increase in temperature shows an increase in diffusivity of lithium at all lithium concentrations in nanoporous and nanosheet structures. The same trend was observed in bulk but only with 0.03 and 0.07 Li ion concentrations.
Thesis (M. Sc. (Chemistry)) -- University of Limpopo, 2019
Keywords: Lithium rechargeable batteries; Nano-architecture structures; Lithium ion batteries; Lithium cells